LITERARY HERITAGE OF AHMEDKHAN NALOYEV: MAJOR MILESTONES IN BIOGRAPHY AND PROBLEMS OF CREATIVITY - L. B. KHAVZHOKOVA (Кавказология, 2021)
The article is devoted to the study of the life and literary heritage of one of the significant creative figures in the Kabardian literature of the 60s – 80s. Of the twentieth century, which determined the features of the formation and development trends of national prose of the specified period. The relevance of the stated topic is due to the fact that until now in the Adygeyan literary criticism there are no generalizing works on the study of milestones in the biography and a comprehensive analysis of the literary work of A. Naloev. The scientific novelty of the research lies in the fact that for the first time a comprehensive substantive and structural-compositional analysis of the writer's works is carried out, starting from the first sketches in the form of miniatures and satirical and humorous stories, ending with larger genres – a story and a novel. The aim of the study is to recreate a complete biographical and creative picture of the life of a talented writer, philologist, educator, educator who raised a whole generation of artists and workers of culture and education. To achieve the goal, a number of tasks are solved, among the main ones – the study of the milestones of the biography of A. Naloev, the analysis of works, the consideration of the ideological and thematic orientation and the genre-style paradigm of the writer's work, determination of the role and place of his creative heritage in national literature and in general in cultural development Adyghe ethnos. The study used general scientific methods with an emphasis on the method of analysis, description and generalization. The results obtained have theoretical significance for further study of national literatures. They can become a significant practical help in writing various kinds of research papers, as well as in the preparation of special courses in universities and colleges.